The Differences in Adjuvant Therapy Effectiveness Meloxicam and N-Acetylcysteine against Negative Symptoms of Schizophrenia - Murda, Banu Kadgada Kalingga; Nugroho, I Gusti Bagus Indro; Herdaetha, Adriesti (Universitas Airlangga, 2023)
Highlights:1. Schizophrenic patients can have negative symptoms.2. Adjuvant therapy is needed to assist antipsychotics in reducing the negative symptoms of schizophrenic patients. AbstractIntroduction: Meloxicam and N-Acetylcysteine are examples of drugs with anti-inflammatory effects that have been widely studied, and are considered to reduce negative symptoms of schizophrenia. Both of these drugs are also widely available in Indonesia and can be obtained at an affordable price. This study aimed to analyze the differences in the effectiveness of adjuvant therapy meloxicam and N-Acetylcysteine on negative symptoms of schizophrenic patients. Methods: This was a quasi-experimental study using a single-blind, pretest–post-test design. Determination of the subject used a purposive sampling technique according to the inclusion criteria. This study examined 34 samples and divided them into two groups. In group A, 17 subjects received adjuvant meloxicam therapy of 15 mg/day for 4 weeks; in group B, 17 subjects received adjuvant therapy of N-Acetylcysteine 400 mg/day for 4 weeks. Score assessment was performed using the positive scale, negative scale, and general psychopathology scale (PANSS) negative subscale pre- and post-therapy, then compared the effectiveness. Data analysis used SPSS 25.0.Results: The mean score of the PANSS post-test subscale was negative in the meloxicam adjuvant therapy group 15.58, while for the N-Acetylcysteine adjuvant therapy group was 17.64 with a p-value of 0.009. The mean decrease in the negative subscale PANSS score in the meloxicam adjuvant therapy group was 11.00, while the N-Acetylcysteine adjuvant therapy group was 19.70 with a p-value of 0.000.Conclusion: There was no difference in the effectiveness of adjuvant therapy meloxicam and N-Acetylcysteine in improving negative symptoms of schizophrenic patients.